STRATEGI KESANTUNAN BERBAHASA DALAM KRITIK PENONTON TERHADAP FILM MERAH PUTIH: ONE FOR ALL DI PLATFORM TIKTOK - Wasi Alya Rizki; Didin Sahidin; Cecep Dudung Julianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of positive and negative criticism and analyze the politeness strategies used by the audience in responding to the film "Merah Putih: One for All" on TikTok social media. The method used is descriptive qualitative with a pragmatic approach. The research data consisted of netizens' comments collected through observation and note-taking techniques, then analyzed using Brown and Levinson's politeness theory. The results showed a polarization of audience responses. Positive criticism tends to focus on ideological aspects, nationalism, and moral messages with a dominance of positive politeness strategies to build solidarity. Conversely, negative criticism dominates discussions on visual technical aspects, asset originality, and marketing, which are often conveyed using bald on record strategies and off-record strategies in the form of sarcasm and humor. This phenomenon indicates that the context of TikTok social media encourages the use of direct and entertaining language styles in conveying film criticism.